Photodissociation dynamics of CH3I probed via multiphoton ionisation photoelectron spectroscopy. Issue 21 (16th May 2019) - Warne, Emily M.; Downes-Ward, Briony; Woodhouse, Joanne; Parkes, Michael A.; Bellshaw, Darren; Springate, Emma; Majchrzak, Paulina; Zhang, Yu; Karras, Gabriel; Wyatt, Adam S.; Chapman, Richard T.; Kirrander, Adam; et al.
Abstract : Femtosecond photoelectron spectroscopy measurements of dissociation CH3 I show complex dynamics in the high energy region of absorption band A. Abstract : The dissociation dynamics of CH3 I is investigated on the red (269 nm) and blue (255 nm) side of the absorption maximum of the A-band. Using a multiphoton ionisation probe in a time-resolved photoelectron imaging experiment we observe very different dynamics at the two wavelengths, with significant differences in the measured lifetime and dynamic structure. The differences are explained in terms of changes in excitation cross-sections of the accessible 3 Q0 and 1 Q1 states and the subsequent dynamics upon each of them. The measurements support the existing literature on the rapid dissociation dynamics on the red side of the absorption maximum at 269 nm which is dominated by the dynamics along the 3 Q0 state. At 255 nm we observe similar dynamics along the 3 Q0 state but also a significant contribution from the 1 Q1 state. The dynamics along the 1 Q1 potential show a more complex structure in the photoelectron spectrum and a significantly increased lifetime, indicative of a more complex reaction pathway.